All-organic luminescent nanodots from corannulene and cyclodextrin nano-assembly: continuous-flow synthesis, non-linear optical properties, and bio-imaging applications. (20th April 2017) - Sreejith, Sivaramapanicker; Menon, Nishanth Venugopal; Wang, Yue; Joshi, Hrishikesh; Liu, Shiying; Chong, Kok Chan; Kang, Yuejun; Sun, Handong; Stuparu, Mihaiela C.
Abstract : Supramolecular interactions between a curved polycyclic hydrocarbon and a cyclic oligosaccharide is shown to furnish functional nanostructures under flow conditions. Abstract : Control of structure and function, at the nanometer scale, remains a formidable challenge in the arena of self-assembled soft materials. Here, we report on the design of a small molecule-based two-component assembly system in which the assembly partners can recognize each other through host–guest interactions. One component is hydrophobic and carries a donor–acceptor type of electronic structure. This is realized by employing a bucky-bowl corannulene derivative. The other component is hydrophilic and hollow. This is achieved by using γ-cyclodextrin, the largest and least studied member of the cyclic oligosaccharide family. In a chemically polar aqueous environment, the two partners come together to form an amphiphilic structure that assembles further into nanosized, quasicrystalline, dot-like, non-toxic, all-organic structures showing two-photon activity and bright green luminescence in water upon excitation at 800 nm. The devised synthesis is achieved by a simple mixing process carried out under continuous-flow conditions. Therefore, in a scalable manner, a constant supply of the assembly components results in continuous fabrication of the nanostructures. Non-linear optical activity and biocompatibility aspects suggest utility of the prepared new class of soft organic nano-dots as contrast agents or labeling tags for visualizing biological specimens. This aspect is examined and demonstrated through two-photon fluorescence imaging of cancer cell lines.